Perpustakaan Nagari Berbasis Inklusi Sosial di Nagari Tigo Koto Silungkang dan Nagari Lawang Kabupaten Agam Sumatera Barat - Elva Rahmah (Universitas Negeri Padang, 2020)
The purpose of the Community Partnership Program is to empower village libraries based on social inclusion so that they can contribute to village development and community empowerment. The library as a social sub-system in society should be a social inclusion institution, anyone can take advantage of library services. To achieve the objectives of the activity, several approaches were carried out including (1) the Participatory Rural Appraisal (PRA) model, (2) the Participatory Technology model, (3) the Community Development model, (4) persuasive namely the approach that was appealing and support without coercion for the community to play an active role in this activity and; (5) educative approach to socialization, training, and assistance as a means of transfer of knowledge and education for community empowerment. The method offered to solve the problem is to carry out socialization, comprehensive training in the management of village libraries based on social inclusion. Through this program, concepts and strategies for developing and empowering village libraries based on social inclusion have been conveyed to village managers, village library managers, and the community. Experience in developing community engagement activities for community empowerment through village libraries in Agam Regency. Participants can understand and commit to following up on the results of the discussion by first preparing a work plan. Communities who receive extension activities can also understand that the Nagari library is not only used as a means to borrow and read books. The village library can be utilized by the community for various activities that can be developed to improve the skills of the village community.